CONDITIONS OF FUNCTIONING AND DEVELOPMENT OF ENTERPRISES IN THE MARKET OF BEEKEEPING PRODUCTS - VINICHENKO, SERHII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the conditions of functioning and development of enterprises in the market of beekeeping products, including economic, legal, social conditions, historical traditions of activity in this field. Beekeeping has been a very attractive sphere of economic activity of households for several millennia. Thus, the development and specialization of beekeeping in Ukraine was formed historically under the influence of climatic and natural conditions. Each natural and climatic zone is characterized by its own direction of economic activity. The beekeeping market in Ukraine is characterized by the presence of about 2.6 million bee colonies, producing 69.9 thousand tons of natural honey. In-depth analysis of the market of honey and other beekeeping products in Ukraine is a prerequisite for the formation and development of effective strategies and tactics marketing for businesses in this industry. Ukraine is among the top ten honey-producing countries in the world and is one of the leaders in terms of exports of bee products. Domestic honey is exported mainly to the United States and EU countries. World honey production has been growing over the last decade, indicating growing demand for honey. The honey market of Ukraine belongs to those where the supply is almost entirely formed by households. According to expert estimates, about 80-100 thousand beekeepers are honey producers in our country. The main market for Ukrainian honey is the EU and the USA. The analysis of the world situation on the honey market shows that the world market of beekeeping products has potential, there is a trend of rising prices for products, which makes this market attractive. Obstacles to achieving high competitiveness and efficiency of honey-producing enterprises have been identified: honey exports mainly as raw materials; lack of state support and bee mortality. Under favorable conditions, Ukraine has the opportunity to increase honey production by a third in the coming years, but this requires existing state programs to support beekeeping and beekeepers’ associations.